Optimation of tempe liquid waste usage for growth performances and feed uptake on Oreochromis niloticus - Andriawan, Soni; Hermawan, David; Rahmania, Shafira (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2024)
Tempe liquid waste (TLW) contains nutrients such as fat, protein, carbohydrates, nitrogen, phosphate, and potassium that could be used in fish rearing. Moreover, it has lactic acid bacteria (LAB) belonging to gram-positive microorganisms, which could decompose organic and inorganic matter in water. Therefore, this study aimed to determine whether TLW could have the potential to enhance Tilapia (Oreochromis niloticus) growth and improve feed efficiency. The study used 180 fish (6.04 ± 0.13 g) reared in twelve aquariums and TLW was obtained from boiling soybeans during the tempe production process in the village of Sanan, Malang. The research design was Completely Randomized Design (CRD), which involved four treatments, T0 (no TLW), T1 (3%), T2 (5%), and T3 (7%) with three replications. The result showed that T2 resulted in the highest growth rate (11.22 ± 0.29 g), specific growth rate (2.07 ± 0.32% / day), feed conversion rate (1.54 ± 0.16), feed efficiency (56.02 ± 1.24%) and survival rate (91.11 ± 0.58%) compared to others. Nonetheless, there was no difference in the absolute length (Lm) parameter at the end of the research. The research results also found that water quality remained favourable for supporting tilapia cultivation under all observed conditions, except for the oxygen levels in the control group, which fell below the standard (<3 mg L-1). Finally, the present study concluded that 5% of TLW could be the best; in contrast, the higher concentration of TLW decreased O. niloticus growth performance, feed efficiency, and survival rate.Keywords: fish development, tilapia, wastewater, water qualities